Gender-Smart Accelerator Challenge Activity Report - Gaba, Morgan; Sani, Ouma; Derenoncourt, Marie Ena; Jaquet, Stéphanie; Grosjean, Godefroy (2022)
This report outlines a Gender-Smart Accelerator Challenge implemented in Senegal in partnership with Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA). The goal of the accelerator is to develop a pipeline of women-led agricultural SMEs operating at different levels of the value chain to be matched with private investment. The report outlines the activity design and process to launch the accelerator and the criteria to identify 20 SMEs for the 6 months capacity building program. Through a needs assessment, the SMEs needs were identified and characterized to inform the program curriculum. The end of the program will be marked by a pitch day where the 20 SMEs will compete for a chance to win a grant of up to $25,000 from CGIAR with the potential matching investment from private actors. Potential financing partners have been identified and will play an active role in determining the winners of the challenge.